Investigating Readability of Texts from the Perspective of Discourse Analysis - Mochamad Rizqi Adhi Pratama; Akbar Syahbana (OKARA: Jurnal Bahasa dan Sastra, 2018)
Investigating readability of texts for use in teaching reading becomes crucial as teachers should adjust the readability of the texts to suit the level of students’ reading skill. If the students learn the inappropriate level of readability of reading texts, it might decrease the success of teaching reading or even the learning of reading might be absent. This paper is aimed at investigating how to analyze readability of the texts in the perspective of discourse analysis; thus, English teachers can choose and apply the appropriate texts as the teaching materials for their students. The objects of this study are three different texts about butterflies taken from three different sources. The study employed descriptive qualitative with concerning the all aspects of the texts which contribute to the readabilities of the texts using Gerot and Wignell (1995) and Eggins’ (2004) theories. Based on the result, there are three central elements of the texts which substantially contribute to the texts’ readabilities such as technical terms, noun phrases, and finiteness. Finally, it is suggested that the teachers analyze the three elements of texts as the consideration in adjusting the texts’ level of readabilities with the students’ level of reading skills.